The development of the Compassion Satisfaction and Compassion Fatigue scale - Halamová, Júlia; Kanovský, Martin; Krizova, Katarina; Šoková, Bronislava; Baránková, Martina; Figley, Charles (Frontiers in Public Health, 2024)
Background: There is a high probability of compassion fatigue occurring in helping professionals who work with traumatized clients or patients. Several instruments exist for measuring compassion fatigue, but all of them have methodological flaws. The original Compassion Satisfaction/Fatigue Self-Test for Helpers is time-consuming and its psychometric properties, including factor structure, have not been supported in the research.Methods: Therefore, the goal of this study was to apply a Mokken scale analysis for polytomous items to shorten the Compassion Satisfaction/Fatigue Self-Test for Helpers and improve its psychometric properties. In addition, we wanted to create norms for the helping professional population. The research sample consisted of 2320 participants from various helping professions with a mean age of 41.74 years (SD=11.62) ranging from 18 to 76 years. Results: To improve scalability, most of the scale items were removed. The resulting item scalability coefficients ranged from 0.349 to 0.655 and Molenaar-Sijtsma reliability coefficient ranged between .75 and .87. The final revised and shortened Compassion Satisfaction and Compassion Fatigue scale (CSCFS) consisted of 5 items for the Compassion Satisfaction -Personal Integrity and Happiness subscale, 5 items for the Compassion Satisfaction -Work Competence and Happiness subscale, 9 items for the Compassion Fatigue -Secondary Traumatic Stress subscale, and 7 for the Compassion Fatigue -Burnout subscale. The newly revised subscales have good reliability coefficients.Conclusions: The CSCFS appears to be a valid and reliable instrument for assessing compassion satisfaction and compassion fatigue among helping professionals. More research is required to support its factor structure in a range of settings. We recommend testing usability across different helping professions and cultures.